Diary Media Towards Students’ Writing Recount Text - Oktaviani Oktaviani; Hastuti Retno Kuspiyah; Muhammad Muklas (Channing : Journal of English Language Education and Literature, 2018)
This objective of this study was to know whether or not there are any significant differences between the students who are taught by using Diary media and the students who are taught by using conventional". And for the study was quantitative research by using an experimental method and quasi-experimental design. Moreover, the population of the study covered the entire of the tenth-grade students of SMA Muhammadiyah 02 Karang Tengah in academic year 2017/2018. It consists of 160 students. And the technique sampling was chosen by purposive sampling. There were two groups they are the experimental group(X-A2) with 32 students and the control group( X-S1) consists of 32 students. In this study, the writer used a written test as an instrument for collecting the data. The data obtained from Independent t-test analysis, between the result of posttest in the experimental group and control group. Based on the calculation by using Independent t-test, the writer found that t obtained was higher than t table (3,531 > 2,000) and less than at the significant level α = 0.05(0.001 < 0.05) in a two-tailed test. So, the null hypothesis (Ho) was rejected and the alternative hypothesis (Ha) was accepted. It can be concluded that any significant differences between the students who are taught by using Diary media and the students who are taught by using conventional media.